The institutional and organizational building of the health protection animal service in the State of Santa Catarina with a view to the health of marine bivalve (Revista de Ciências Agroveterinárias, 2011)
The malacocultura consists of occupation profits for many families and represents a business risk activity for the occurrence of diseases. Historically, countries that are important producers of bivalves suffered with the failure of the crops due to diseases. The study aimed to understand the structure, operations and technical knowledge of the veterinary service of the executing agency for the animal health official service in the State of Santa Catarina, from January to March 2009. In this sense, the method used was interviews structured and unstructured, as well as direct observation with the involvement of the researcher at the hearings and observation in aquatic animal health actions carried out by the official service, but without the interference of the researcher in these actions. It was concluded by the proposed method, there is no evidence of specific actions in the field of health protection of farmed marine bivalves during the study period.
Keywords: Malacoculture; Veterinary service; Animal health.